2008
DOI: 10.1007/s00436-008-1003-7
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen branching enzyme: a novel deltamethrin resistance-associated gene from Culex pipiens pallens

Abstract: The glycogen branching enzyme (GBE) gene has been cloned from Culex pipiens pallens. An open reading frame of 2,070 bp was found to encode a putative 689 amino acid protein. The deduced amino acid sequence shares 82% and 60% identity with GBE genes from Aedes aegypti and Homo sapiens. Transcript expression of GBE was determined by real-time polymerase chain reaction in deltamethrin-susceptible and deltamethrin-resistant strains of the Culex mosquito. The results demonstrated that this gene has 19.7-fold higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Pipiens pallens . As a result, several genes associated with novel DM resistance have been isolated [17-19]. One of the highly expressed genes in the DR strain was opsin, which belongs to G protein-coupled receptors (GPCRs) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Pipiens pallens . As a result, several genes associated with novel DM resistance have been isolated [17-19]. One of the highly expressed genes in the DR strain was opsin, which belongs to G protein-coupled receptors (GPCRs) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report the characterization of one cypermethrin resistance associated gene of C. pipiens pallens. The writer reported insecticide-resistant ribosomal protein L39 gene of C. pipiens pallens , while other researchers in the same laboratory identified several genes differentially expressed in cypermethrin-resistant strain of the mosquito previously (Chen et al 2010;Gong et al 2005a,b;He et al 2009;Hu et al 2007;Shen et al 2002;Tian et al 2001;Xu et al 2008;Yang et al 2008;Zhang et al 2011;Zhu et al 1998Zhu et al , 2000Sun et al 2006). Some of the candidate genes encode for enzymes such as chymotrypsin (Gong et al 2005a), trypsin (Shen et al 2002), and CYP450 (Gong et al 2005b), which are likely involved in more direct functions, e.g., oxidation of cypermethrin, others are likely more upstream factors, such as ribosomal protein L22 (He et al 2009), ribosomal protein S4 , and ribosomal protein S29 .…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, searches of the ten most highly expressed genes from these previous studies with our data found that none of these previously identified genes were overexpressed in our resistant strains. Candidate genes previously associated with pyrethroid resistance in other species of mosquitoes include transferrin [ 82 ], iron responsive element binding protein [ 83 ], glycogen branching enzyme [ 84 ], chymotrypsin [ 82 ] and G-protein coupled receptor [ 85 ]. None of these genes were overexpressed in our resistant strains, leading us to conclude that they do not play a role in pyrethroid resistance in CKR or SP.…”
Section: Discussionmentioning
confidence: 99%